The Development of Fatwas Based on Local Wisdom to the National Level: A Case Study of Panaik Money Fatwa - Syatar, Abdul; Bakry, Muammar; Bedong, M. Ali Rusdi; Ahmad, Ahmad; Pallawagau, Baso (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
The fatwa of the Indonesian Ulema Council of South Sulawesi Province regarding panaik money is debated and considered cynical by some people who feel disturbed. The cultural shift in